Along for the ride : a novel - Dessen, Sarah (Speak, 2011)
Auden gets a chance to recapture the carefree teen life she missed while her parents were going through a divorce when she goes to spend the summer with her dad and his new family in a charming beach town and meets fellow insomniac Eli, an intriguing loner fighting demons of his own.